2016
DOI: 10.3791/53255
|View full text |Cite
|
Sign up to set email alerts
|

Use of Galvanic Skin Responses, Salivary Biomarkers, and Self-reports to Assess Undergraduate Student Performance During a Laboratory Exam Activity

Abstract: Typically, self-reports are used in educational research to assess student response and performance to a classroom activity. Yet, addition of biological and physiological measures such as salivary biomarkers and galvanic skin responses are rarely included, limiting the wealth of information that can be obtained to better understand student performance. A laboratory protocol to study undergraduate students' responses to classroom events (e.g., exams) is presented. Participants were asked to complete a represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…A method based on SNS physiology, electrodermal activity (EDA), has been widely used in emotions-based research (Bouscein, 2012;D'Mello & Graesser, 2014;Harley et al, 2013;Harley et al, 2015;Villanueva et al, 2014;Villanueva, Valladares, & Goodridge, 2016). EDA is measured in locations where sweat glands are most dense (e.g., fingers, palms, or regions connecting the second and third or fourth and fifth fingers of the hand) and regions with a large number of innervated fibers that connect to the SNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A method based on SNS physiology, electrodermal activity (EDA), has been widely used in emotions-based research (Bouscein, 2012;D'Mello & Graesser, 2014;Harley et al, 2013;Harley et al, 2015;Villanueva et al, 2014;Villanueva, Valladares, & Goodridge, 2016). EDA is measured in locations where sweat glands are most dense (e.g., fingers, palms, or regions connecting the second and third or fourth and fifth fingers of the hand) and regions with a large number of innervated fibers that connect to the SNS.…”
Section: Discussionmentioning
confidence: 99%
“…All EDA participants were asked to wear a clean wrist band 1 hr before the start of each engineering design method workshop topic to create enough sweat build-up on their wrists to gather baseline EDA data (Nourbakhsh, Wang, & Chen, 2013;Nourbakhsh, Wang, Chen, & Calvo, 2012;Paletta, Pittino, Schwarz, Wagner, & Kallus, 2015;Shi, Ruiz, Taib, Choi, & Chen, 2007;Sinha, Gavas, Chatterjee, Das, & Sinharay, 2015;Villanueva, Raikes, Ruben, Schaefer, & Gunther, 2014;Villanueva et al, 2016). Ten minutes before class, a member of the research team fitted an Empatica E3 EDA sensor (Empatica, Boston, MA) on each participant and recorded the sensor identification number.…”
Section: Eda Collectionmentioning
confidence: 99%
“…Circulating cortisol levels increase in response to physical and psychological activation; thus, it is used as a biomarker of a stress response (Kirschbaum, Pirke, & Hellhammer, 1993;Lighthall, Gorlick, Schoeke, Frank, & Mather, 2013;McEwen, 1998;Stephens, Mahon, McCaul, & Wand, 2016). While other measures of stress exist, including serum cortisol, galvanic skin response, heart rate, and blood pressure (Campbell & Ehlert, 2012;Villanueva, Valladares, & Goodridge, 2016), these other measures typically are utilized within laboratory settings due to the need for aseptic techniques, machines, or continuous sensor leads connected to individual participants throughout the evaluation process. In contrast, the use of salivary cortisol readily lends itself to the formal classroom setting where less-invasive and least restrictive environmental conditions are desired to enable the simultaneous evaluation of many students.…”
Section: Stress Cortisol and Learningmentioning
confidence: 99%
“…Villanueva and colleagues have reported using self-reports with electrodermal activity sensors [19], [20] while Goodridge, Call, and colleagues have used electroencephalogram monitors [21], [22] to study performance in an engineering statics course. Each study has developed methods to identify how the type of exam problem could influence the activation of students' pre-frontal cortex and EDA arousal [19]- [22], which influence student performance and learning of different engineering problems.…”
Section: Academic Emotions In Authentic Engineering Educationmentioning
confidence: 99%
“…Villanueva and colleagues have reported using self-reports with electrodermal activity sensors [19], [20] while Goodridge, Call, and colleagues have used electroencephalogram monitors [21], [22] to study performance in an engineering statics course. Each study has developed methods to identify how the type of exam problem could influence the activation of students' pre-frontal cortex and EDA arousal [19]- [22], which influence student performance and learning of different engineering problems. Some electroencephalography (EEG) research and theory such as that found in the neural efficiency hypothesis seek to identify periods of focus in study participants and when considered in context with academic emotion data collection [23] may yield important information about a student's performance on an exam in real-time.…”
Section: Academic Emotions In Authentic Engineering Educationmentioning
confidence: 99%